2017
DOI: 10.1111/1751-7915.12756
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling biocomplexity of electroactive biofilms for producing hydrogen from biomass

Abstract: SummaryLeveraging nature's biocomplexity for solving human problems requires better understanding of the syntrophic relationships in engineered microbiomes developed in bioreactor systems. Understanding the interactions between microbial players within the community will be key to enhancing conversion and production rates from biomass streams. Here we investigate a bioelectrochemical system employing an enriched microbial consortium for conversion of a switchgrass‐derived bio‐oil aqueous phase (BOAP) into hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…The end-products of fermentation such as acetate, form substrate for the exoelectrogens and accumulate if an electron sink is not provided such as under open circuit conditions. Thus, the syntrophy between the two groups was clearly illustrated (Lewis et al, 2018).…”
Section: Bioelectrochemistry Of Primary Reactions Leading To Electroamentioning
confidence: 94%
See 4 more Smart Citations
“…The end-products of fermentation such as acetate, form substrate for the exoelectrogens and accumulate if an electron sink is not provided such as under open circuit conditions. Thus, the syntrophy between the two groups was clearly illustrated (Lewis et al, 2018).…”
Section: Bioelectrochemistry Of Primary Reactions Leading To Electroamentioning
confidence: 94%
“…The information on complex microbial communities present in bioanode treating mixed substrate feedstocks is limited. Lewis et al recently reported characterization of microbial population treating switchgrass-derived BOAP, which showed a dependence between the fermenters and the exoelectrogens (Lewis et al, 2018). This was one of the first detailed account of the microbial community treating complex feedstocks directly fed into anode.…”
Section: Bioelectrochemistry Of Primary Reactions Leading To Electroamentioning
confidence: 99%
See 3 more Smart Citations